2005
DOI: 10.1007/s10789-005-0307-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Vaterite-to-Calcite Phase Transition under Sonication

Abstract: INTRODUCTIONCalcium carbonate, a material of considerable practical importance [1][2][3], exists in two anhydrous, metastable polymorphs (vaterite and aragonite) and one stable (under ordinary conditions) polymorph (calcite). Each of these polymorphs can be prepared in the form of particles of different morphologies. As a rule, vaterite particles are spheroidal and calcite particles are rhomboidal [4, 5].The vaterite-to-calcite phase transition [6,7] is believed to occur either through spontaneous recrystalliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…27 These conditions have not been reproduced yet and most of the work is done at lower ultrasonic frequencies (kHz).…”
Section: ■ Discussionmentioning
confidence: 99%
“…27 These conditions have not been reproduced yet and most of the work is done at lower ultrasonic frequencies (kHz).…”
Section: ■ Discussionmentioning
confidence: 99%
“…However, a shortening of the induction time for vaterite formation, caused by applying more intensive agitation and seen as a pH drop, can be observed (ultrasonic < magnetic < mechanical). At that, the most likely mechanism of the promotion of nucleation in the case of sonication is a collapse of cavitation bubbles, which caused localized high pressure and temperature spots, while the literature data indicated that the energetic collisions among particles may enhance the transition of metastable vaterite to calcite as well [42][43][44][45]. In addition, the SEMs of the respective samples isolated after 5 days of aging ( Figure SI8) showed significantly different morphologies of calcite crystals.…”
Section: Synthesis and Characterization Of Thin Tabular {001} Calcitmentioning
confidence: 95%
“…9 The vaterite-tocalcite phase transition has been observed in spheroidal vaterite particles produced by reacting aqueous Ca(NO 3 ) 2 and Na 2 CO 3 solutions at 20 AE 1 C under 2.6-MHz sonication. 10 The high-pressure form of calcium carbonate (aragonite) has been obtained by the transformation of calcite to aragonite at a pressure of 6.16 GPa and a temperature of 345 C. 11 Vaterite is rarely found in nature as a mineral but it exists in biological tissues (e.g., mollusks) and some sediments. 12 The vaterite phase has higher solubility in aqueous solution, which plays an important role in the formation of apatite in a simulated body fluid.…”
Section: Introductionmentioning
confidence: 99%